2003
DOI: 10.1002/ajim.10269
|View full text |Cite
|
Sign up to set email alerts
|

Serum pneumoproteins: A cross‐sectional comparison of firefighters and police

Abstract: Firefighters have lower serum concentrations of SP-A than do police. Although the clinical significance of this finding is presently unknown, SP-A deserves further study as a biomarker of toxic exposure to the lower respiratory tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Contrary to expectations, no clear associations were found between exposure and serum pneumoprotein levels. Serum pneumoproteins have been used as biomarkers in studies on exposure to respiratory irritants such as tobacco‐smoke [Bernard et al, 1994; Robin et al, 2002], trichloramines [Carbonnelle et al, 2002], and fire smoke [Bernard et al, 1997; Burgess et al, 2001, 2003]. Previously, we found that CC16 and SP‐A levels in serum are very stable within persons, whereas differences between individuals can be large [Greven et al, 2011a].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to expectations, no clear associations were found between exposure and serum pneumoprotein levels. Serum pneumoproteins have been used as biomarkers in studies on exposure to respiratory irritants such as tobacco‐smoke [Bernard et al, 1994; Robin et al, 2002], trichloramines [Carbonnelle et al, 2002], and fire smoke [Bernard et al, 1997; Burgess et al, 2001, 2003]. Previously, we found that CC16 and SP‐A levels in serum are very stable within persons, whereas differences between individuals can be large [Greven et al, 2011a].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several lung‐specific proteins, such as Clara cell protein (CC16) and surfactant protein A (SP‐A), have been proposed as new biomarkers for lung epithelial injury following exposure to airway irritants [Hermans and Bernard, 1999]. Serum pneumoprotein levels have been used as biomarkers in studies of exposure to general air pollution [Berthoin et al, 2004], respiratory irritants like trichloramines [Carbonnelle et al, 2002] and fire smoke [Bernard et al, 1997; Burgess et al, 2001, 2002, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Both firefighters and police officers perform full-time work, and it is presumed that the police have a very limited or no exposure compared with firefighters, because they do not work in fire zones. Police officers and firefighters have similar demographic characteristics with respect to socioeconomic status, access to healthcare, retirement benefits, and physical entry require-ments, and they have been used in epidemiological studies before [Kern et al, 1993;Burgess et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps due to epithelial damage in the lung, circulating CC16 levels increase following acute environmental exposures such as smoking a cigarette or firefighting [ 7 , 8 ]. However, overall circulating levels are lower in those with chronic environmental exposures, such as smokers or firefighters, compared to the general population [ 9 , 10 ]. It has been hypothesized that those with chronic exposures may have fewer or less responsive club cells in their lungs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%